Prostaglandin F2α stimulates the growth of human intermediate hair follicles in ex vivo organ culture with potential clinical relevance - Miranda, Ben H.; Khidhir, Karzan G.; Tobin, Desmond J. (Frontiers in Physiology, 2025)
BackgroundHair plays a crucial role in social and sexual communication; hair disorders such as alopecia or hirsutism can therefore cause psychological distress. Current treatments are limited by unwanted side effects and a lack of understanding of hair follicle (HF) regulation, particularly in miniaturised intermediate or vellus-like follicles; the clinical targets in hair loss disorders. The discovery that bimatoprost, a prostamide F2α analogue, stimulates eyelash growth suggest a possible role for other prostanoids in hair growth.ObjectivesTo evaluate the impact of the naturally occurring prostaglandin F2α (PGF2α) on human intermediate HF growth, comparing the effects on matched terminal and intermediate follicles using a pre-clinical ex vivo organ culture model. Furthermore, to determine the involvement of PGF2α receptors (FP) and their location within both these HF types.MethodsMatched human female pre-auricular facelift skin HFs were incubated with PGF2α alone or in combination with an FP antagonist for 9 days in the gold-standard ex vivo HF organ culture model. To confirm FP gene expression in both terminal and intermediate lower HF bulbs, RT-PCR was performed using specific FP primers, confirmed by sequence analysis. Immunohistochemistry was conducted using frozen sections to locate the FP protein in HF components.ResultsPGF2α (100 nM) stimulated terminal HF fibre growth by 4.93% (p = 0.019) with a greater effect (10.03% (p < 0.001) stimulation) on intermediate HFs. PGF2α stimulation significantly prolonged anagen (the growth phase of the hair cycle) duration in both HF types and to similar extent. These increases in hair fibre elongation were blocked by the receptor (FP) antagonist in both terminal and intermediate follicles. RT-PCR confirmed FP gene expression and immunohistochemistry located FP protein in the dermal papilla and connective tissue sheath of both intermediate and terminal HFs.ConclusionWe demonstrate, for the first time, that PGF2α stimulates human HF growth in organ culture via a receptor-driven mechanism, probably directly affecting the follicles’ regulatory dermal papilla function. The greater response of intermediate, compared to matched terminal, HFs suggests potential future clinical significance for medical conditions such as alopecia, or insufficient beard growth, and promoting hair growth in ‘relatively hairless’ donor graft skin or transplant follicles after elective, trauma or burn injury surgical reconstruction.